Increased endothelin-1 reactivity and endothelial dysfunction in carotid arteries from rats with hyperhomocysteinemia - de Andrade, CR (Blackwell Publishing Ltd, 2009)
BACKGROUND AND PURPOSE: There are interactions between endothelin-1 (ET-1) and endothelial vascular injury in hyperhomocysteinemia (HHcy), but the underlying mechanisms are poorly understood. Here we evaluated the effects of HHcy on the endothelin system in rat carotid arteries. EXPERIMENTAL APPROACH: Vascular reactivity to ET-1 and ET(A) and ET(B) receptor antagonists was assessed in rings of carotid arteries from normal rats and those with HHcy. ET(A) and ET(B) receptor expression was assessed by mRNA (RT-PCR), immunohistochemistry and binding of [(125)I]-ET-1. KEY RESULTS: HHcy enhanced ET-1-induced contractions of carotid rings with intact endothelium. Selective antagonism of ET(A) or ET(B) receptors produced concentration-dependent rightward displacements of ET-1 concentration response curves. Antagonism of ET(A) but not of ET(B) receptors abolished enhancement in HHcy tissues. ET(A) and ET(B) receptor gene expressions were not up-regulated. ET(A) receptor expression in the arterial media was higher in HHcy arteries. Contractions to big ET-1 served as indicators of endothelin-converting enzyme activity, which was decreased by HHcy, without reduction of ET-1 levels. ET-1-induced Rho-kinase activity, calcium release and influx were increased by HHcy. Pre-treatment with indomethacin reversed enhanced responses to ET-1 in HHcy tissues, which were reduced also by a thromboxane A(2) receptor antagonist. Induced relaxation was reduced by BQ788, absent in endothelium-denuded arteries and was decreased in HHcy due to reduced bioavailability of NO. CONCLUSIONS AND IMPLICATIONS: Increased ET(A) receptor density plays a fundamental role in endothelial injury induced by HHcy. ET-1 activation of ET(A) receptors in HHcy changed the balance between endothelium-derived relaxing and contracting factors, favouring enhanced contractility. British Journal of Pharmacology (2009) 157, 568–580; doi:10.1111/j.1476-5381.2009.00165.x; published online 9 April 2009 This article is part of a themed section on Endothelium in Pharmacology. For a list of all articles in this section see the end of this paper, or visit: http://www3.interscience.wiley.com/journal/121548564/issueyear?year=2009